Digestion products of the PH20 hyaluronidase inhibit remyelination. Issue 2 (5th March 2013) - Preston, Marnie; Gong, Xi; Su, Weiping; Matsumoto, Steven G.; Banine, Fatima; Winkler, Clayton; Foster, Scott; Xing, Rubing; Struve, Jaime; Dean, Justin; Baggenstoss, Bruce; Weigel, Paul H.; et al.
<x xml:space="preserve">Abstract</x> Objective Oligodendrocyte progenitor cells (OPCs) recruited to demyelinating lesions often fail to mature into oligodendrocytes (OLs) that remyelinate spared axons. The glycosaminoglycan hyaluronan (HA) accumulates in demyelinating lesions and has been implicated in the failure of OPC maturation and remyelination. We tested the hypothesis that OPCs in demyelinating lesions express a specific hyaluronidase, and that digestion products of this enzyme inhibit OPC maturation. Methods Mouse OPCs grown in vitro were analyzed for hyaluronidase expression and activity. Gain of function studies were used to define the hyaluronidases that blocked OPC maturation. Mouse and human demyelinating lesions were assessed for hyaluronidase expression. Digestion products from different hyaluronidases and a hyaluronidase inhibitor were tested for their effects on OPC maturation and functional remyelination in vivo. Results OPCs demonstrated hyaluronidase activity in vitro and expressed multiple hyaluronidases, including HYAL1, HYAL2, and PH20. HA digestion by PH20 but not other hyaluronidases inhibited OPC maturation into OLs. In contrast, inhibiting HA synthesis did not influence OPC maturation. PH20 expression was elevated in OPCs and reactive astrocytes in both rodent and human demyelinating lesions. HA digestion products generated by the PH20 hyaluronidase but not another hyaluronidase inhibited remyelination following lysolecithin‐induced demyelination. Inhibition of hyaluronidase activity lead to increased OPC maturation and promoted increased conduction velocities through lesions. Interpretation We determined that PH20 is elevated in demyelinating lesions and that increased PH20 expression is sufficient to inhibit OPC maturation and remyelination. Pharmacological inhibition of PH20 may therefore be an effective way to promote remyelination in multiple sclerosis and related conditions. ANN NEUROL 2013;73:266–280